2004
DOI: 10.1007/s10038-004-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of an intragenic microsatellite marker in the CC16 gene with asthma in the Indian population

Abstract: The gene for Clara cell secretory protein (CC16) is an ideal candidate for investigating genetic predisposition to asthma because of its role in the airway as an antiinflammatory molecule, differences in its levels between asthmatics and healthy controls, and its genetic location (11q13). We investigated the association of an SNP (A38G) and an intragenic repeat polymorphism in the CC16 gene with asthma and its associated traits, such as total serum IgE levels, in a case control as well as in a family based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…The effects of genetic variants in or near the CC16 and SP-D coding genes on circulating levels of their respective proteins have been previously reported (19,44,45) and the genetic variants in corresponding genes were also listed among the top SNPs in our study. However, there were remote genetic loci affecting the levels of CC16 and SP-D, which have no significant linkage disequilibrium with SNPs in the biomarker coding genes.…”
Section: Discussionsupporting
confidence: 52%
“…The effects of genetic variants in or near the CC16 and SP-D coding genes on circulating levels of their respective proteins have been previously reported (19,44,45) and the genetic variants in corresponding genes were also listed among the top SNPs in our study. However, there were remote genetic loci affecting the levels of CC16 and SP-D, which have no significant linkage disequilibrium with SNPs in the biomarker coding genes.…”
Section: Discussionsupporting
confidence: 52%
“…The associations between the risk of asthma and gene polymorphisms, such as single nucleotide polymorphism (SNPs), have been studied extensively. Recently, a number of studies have investigated the association between the risk of asthma and the CC16 gene A38G polymorphism (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on humans and rats have shown that CC16 is a sensitive biomarker of respiratory epithelial injury in exposures to welder fumes, glutaraldehyde, nitric oxides, or Al foundry dusts [18][19][20][21][22][23]. Clara cell proteins are involved in the pathogenic mechanisms leading to fibrosis [15,24], chronic obstructive pulmonary disease (COPD) [25,26], and asthma in humans [27][28][29] and in murine asthma model [30,31]. Low level of CC16 was observed in serum and bronchoalveolar lavage fluid (BAL) of active smokers [32].…”
Section: Introductionmentioning
confidence: 99%